Microleakage Study of a Bulk Fill over an Uncured Adhesive System - Pinto, Mariana Vaz (2023)
This study aimed to evaluate and compare the microleakage of composite resin restorations under a total-etch adhesive system applied with two different techniques, with and without cure. Cavities were made on the buccal surface of twenty-six intact teeth and subsequently restored with bulk-fill flow composite resin (SDR®® flow+) and conventional resin (Spectra™ ST HV). Two experimental groups were created, one where the total-etch adhesive (Prime & Bond Active®) was cured and another where the adhesive was not cured before placing the flowable resin. Two control groups were also created, negative and positive. After the restorations were finished the, teeth were submerged in a solution of sodium pertechnetate (99mTcNaO4) for 3 h to evaluate the microleakage. The results showed more infiltration of radioisotopes characterized by the highest total count values of microleakage in group 1 (cured adhesive) and in the positive control. Group 2 (noncured adhesive) and the negative control showed lower values. We therefore considered that these groups were similar since their p-value was less than 0.05, with no statistically significant difference. Group 4 showed a statistically significant increase in relation to group 3 (p = 0.027). We concluded that the method of bulk-fill composite resins with noncured adhesive agents can have a positive effect on the longevity of bond strengths, with reduced microleakage.